The Influence Of Servant Leadership And Intrinsic Motivation On Employee Job Satisfaction At Stikes Sapta Bakti Bengkulu - Ryndry Andika; Ida Ayu Made E G; Wagini Wagini (Journal of Management, Economic, and Accounting, 2026)
Job satisfaction is an essential factor that determines employee performance and organizational success, including in higher education institutions such as STIKes Sapta Bakti Bengkulu. This study aims to determine the influence of Servant Leadership and Intrinsic Motivation, both partially and simultaneously, on Employee Job Satisfaction at STIKes Sapta Bakti Bengkulu. The research uses a quantitative approach with descriptive analysis. The population consists of all lecturers and administrative staff totaling 50 respondents, who were also used as the sample through a total sampling technique. Data were analyzed using multiple linear regression through SPSS version 27, including validity and reliability tests, t-test, F-test, and coefficient of determination. The results show that Servant Leadership has a positive and significant effect on Job Satisfaction with a t-value = 6.622 and sig < 0.001. Intrinsic Motivation also has a positive and significant effect on Job Satisfaction with a t-value = 2.109 and sig = 0.000. Simultaneously, both variables significantly affect Job Satisfaction with an F-value = 55.029 and sig = 0.000. The Adjusted R Square value = 0.701, indicating that 70.1% of job satisfaction variation is explained by both independent variables, while the remaining 29.9% is influenced by other factors.